Teologi Bencana dalam Perspektif M. Quraish Shihab - Khafidhoh Khafidhoh (UIN Sunan Kalijaga Yogyakarta, 2013)
Human life has always been dealt with various disasters from earthquake, tsunami to volcano eruption. In the past, as listed in the Qur’an, a lot of stories depicted the vanished people of unbeliever. While the cases of unbeliever referred to the punishment of Alloh, the query is whether the disaster happened to the Believer served as the Divine punishment. Two questions are discussed in this research: (1) How Quraish Shihab interpreted the verses of disaster?, and (2) What is the theology of disaster in Quraish Shihab’s Tafsir al-Misbah? The research shows that natural disaster occurred, in Quraish Shihab’s view, due to the imbalance of environment. Alloh has created harmonious environment, but human being tends to conduct chaos and destruction. Disaster could be concluded into three: (1) disaster that denoted collective destruction, (2) disaster that related to the destruction of meaning, and (3), disaster that dealt with the danger. The cause of disaster could be categorized into three, namely, (1) disaster due to the will of God (2) disaster due to human error (3) disaster due to the wickedness of human. Pertaining to the ethics facing disaster, one could refer to istirja’, patience, learning, the obedience to Alloh. The lesson learned from the disaster are among others, (1) individual aspect : (a) increasing the degree of faith, (b) supporting one’s proximity to God, (c) realizing the love of God, (d) situating one’s faith and (e) supporting one’s humility and (2) social one, building solidarity among human beings.